TAFSIR AMALY SEBAGAI TAFSIR SUFI KARYA MUHAMMAD QOYYIM YA’QUB - Ali Mustofa (STAI Darussalam Lampung, 2023)
This objective is to discuss Tafsir Amaly as a Sufi interpretation. This research uses descriptive qualitative research methods. The results of the study state that Tafsir Amaly is a Sufi interpretation, Sufi interpretation departs from the assumption that the Qur'an has both zahir and batin meanings. There are three components of the epistemological study of interpretation: interpretation sources, interpretation techniques, and interpretation validity. Tafsir Amaly draws its sources from the Qur'ān, hadith, and laduni science, and uses the ijmali method and isyari approach. Kyai Qoyyim uses linguistic rules such as sorof and nahwu analysis to interpret verses. They also use takwil to find out the inner meaning of a verse. From this takwil, Kyai Qoyyim produces a practical interpretation.